Carbohydrate antigen 125 in congestive heart failure: ready for clinical application? - Feng, Rui; Zhang, Zhenlu; Fan, Qingkun (Frontiers in Oncology, 2023)
The Word count:10258 (Include references), 7047 (References are not included)【 Abstract 】 Congestion is the permanent mechanism driving disease progression in patients with acute heart failure (AHF) and also is an important treatment target. However, distinguishing between the two different phenotypes (intravascular congestion and tissue congestion) for personalized treatment remains challenging. Historically, carbohydrate antigen 125 (CA125) has been a frequently used biomarker for the screening, diagnosis, and prognosis of ovarian cancer. Interestingly, CA125 is highly sensitive to tissue congestion and shows potential for clinical monitoring and optimal treatment of congestive heart failure (HF). Furthermore, in terms of right heart function parameters, CA125 levels are more advantageous than other biomarkers of HF. CA125 is expected to become a new biological alternative marker for congestive HF and thereby is expected be widely used in clinical practice.